CD99 Chimeric antigen receptor T-Cell Therapy in the treatment of adult Rhabdomyosarcoma: A case report and literature review - Li, Hui; Long, Ping; Wei, Xinyu; Zhou, Meng; Yin, Mengqing; Wu, Huixian; Zhu, Haichuan; Zhu, Ming; Feng, Lei; Li, Ming; Wu, Qin; Zhang, Tongcun; et al. (Current problems in cancer. Case reports, 2025)
•CD99 is overexpressed in various malignant tumors, including Ewing's sarcoma and hematological cancers. CAR-T cell therapy was used for targeted treatment in an adult patient with malignant peripheral schwannoma and embryonal rhabdomyosarcoma. Despite postoperative complications and intolerance to radiation therapy, CAR-T cell therapy targeting CD99 is well tolerated and stabilized the disease for 13 months, highlighting its potential as a novel treatment for refractory sarcomas. CD99 is a transmembrane protein overexpressed in tumor tissues, particularly in Ewing’s sarcoma. Recent studies have highlighted distinct patterns of CD99 expression in various malignancies, including gliomas, osteosarcoma, and breast and pancreatic cancers. CD99 is also expressed in hematopoietic cell lines, with differential expression in hematological malignancies such as T-cell acute lymphoblastic leukemia and acute myeloid leukemia, suggesting its potential as a therapeutic target. We report the case of an adult patient with a malignant peripheral nerve sheath tumor of the left thigh with embryonal rhabdomyosarcoma and adenoid differentiation. The patient underwent R0 resection surgery but experienced complications, including infection and poor wound healing, and was unable to tolerate radiotherapy. Postoperative pathological analysis revealed CD99 positivity. Given the lack of response to conventional treatments, the patient underwent CD99-targeted chimeric antigen receptor T (CAR-T) cell therapy. The therapy was well-tolerated, with only mild cytokine release syndrome (CRS), and resulted in disease stabilization over 13 months of follow-up. This case demonstrates the potential of CD99-targeted CAR-T cell therapy as a novel and effective treatment for adult rhabdomyosarcoma. These findings suggest that CD99-CAR-T cell therapy warrants further investigation as a therapeutic option for refractory sarcomas.